Passivity in Aesthetic Experience: Husserlian and Enactive Perspectives. Issue 1 (2nd January 2019) - Høffding, Simon; Roald, Tone
ABSTRACT: This paper argues that the Husserlian notion of "passive synthesis" can make a substantial contribution to the understanding of aesthetic experience. The argument is based on two empirical cases of qualitative interview material obtained from museum visitors and a world-renowned string quartet, which show that aesthetic experience contains an irreducible dimension of passive undergoing and surprise. Analyzing this material through the lens of passive syntheses helps explain these experiences, as well as the sense of subject–object fusion that occurs in some of the most intense forms of aesthetic experience. These analyses are then contrasted with a potentially contradicting take on aesthetic experience from a recent trend in cognitive science, namely enactive aesthetics, which insists on the active subjective construction and sense-making of aesthetic experience. Finally we show that the two positions are in fact compatible.